Chinese for the world level 2 (Singapore : Times Publishing Ltd., 1997)
The Times Lingua : Chinese for the world course has three outstanding features. Firstly, and most importantly, it is convenient for self study, secondly, the contents are topic-centered, covering aspects of everyday life. Thirdly, is course lays a foundation for learners of Chinese.
Standard set level 2
Keywords: Chinese language